2010
DOI: 10.1007/s00425-010-1128-7
|View full text |Cite
|
Sign up to set email alerts
|

Thermal clamping of temperature-regulating flowers reveals the precision and limits of the biochemical regulatory mechanism

Abstract: The flowers of several families of seed plants warm themselves when they bloom. In some species, thermogenesis is regulated, increasing the rate of respiration at lower ambient temperature (T (a)) to maintain a somewhat stable floral temperature (T (f)). The precision of this regulation is usually measured by plotting T (f) over T (a). However, such measurements are influenced by environmental conditions, including wind speed, humidity, radiation, etc. This study eliminates environmental effects by experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 34 publications
0
35
0
1
Order By: Relevance
“…In some thermogenic plants, floral temperature is maintained at a constant range, independent of ambient temperature, for a long period throughout anthesis [8],[35],[36]. Floral temperature stability of these plants is achieved by means of physiological thermoregulation [35],[36]. In this study, floral temperature of M. sprengeri changed constantly throughout anthesis and major thermogenic episodes were short, which indicated that M. sprengeri was not thermoregulated.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In some thermogenic plants, floral temperature is maintained at a constant range, independent of ambient temperature, for a long period throughout anthesis [8],[35],[36]. Floral temperature stability of these plants is achieved by means of physiological thermoregulation [35],[36]. In this study, floral temperature of M. sprengeri changed constantly throughout anthesis and major thermogenic episodes were short, which indicated that M. sprengeri was not thermoregulated.…”
Section: Discussionmentioning
confidence: 64%
“…Distinct heating patterns have been reported in different thermogenic species [35],[36]. In some thermogenic plants, floral temperature is maintained at a constant range, independent of ambient temperature, for a long period throughout anthesis [8],[35],[36]. Floral temperature stability of these plants is achieved by means of physiological thermoregulation [35],[36].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests both S. renifolius and A. maculatum utilize this enzyme to provide reducing equivalents to the ubiquinone pool; however, S. renifolius , with less abundance of NDB, may depend more on NDA than A. maculatum . In S. renifolius , the difference between the floral and ambient temperature has been found to show a positive correlation with CO 2 production in the regulation of floral temperature [34]. As the CO 2 is presumably produced during TCA (tricarboxylic acid) cycle activity, the re-oxidation of NADH within the mitochondrial compartment is vital for maintaining cycle turnover, particularly at low ambient temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…The 800 mL chamber itself consisted of a miniature constant temperature (CT) cabinet, described earlier in detail (Seymour et al . ). In brief, the cabinet was heated or cooled by a Peltier plate and heat sink on one wall, and the air in the chamber was circulated with a small fan.…”
Section: Methodsmentioning
confidence: 97%
“…The effect of ambient P o 2 on respiration rate was measured with open‐flow respirometry described previously (Seymour et al . ), but using a fuel cell O 2 analyser (David Bishop Instruments, Heathfield, UK; model 280). Instead of drawing atmospheric air into the respirometry chamber by suction and measuring flow on the downstream side as previously done, pressurized gas mixtures were supplied at measured rates to the upstream side of the chamber.…”
Section: Methodsmentioning
confidence: 99%